Implementation of a low-cost IoT system for a Hermle UWF900E CNC milling machine - Berrocal-Campos, Daniel (Instituto Tecnológico de Costa Rica, 2018)
This inform summarizes the work executed for designing, building and testing a custom, low-cost monitoring system for a CNC milling center model Hermle UWF900E. The structure proposed follows the general topology of an IoT application, with the intention of making access and data collection easier. The variables monitored were chosen as a combination of basic working conditions, safety parameters and environmental factors that could a ect the operation. The stages involved in the project development included theoretical research, to nd the adequate protocols and components to use; electrical circuit design, including sensor calibration and controller programming; and Internet communication deployment, involving both a web-based database storage and web-page working as user interface. Each stage included a series of tests to prove individual performance of the parts involved. After installing the whole system, real operative data was recorded during a period of 2 weeks, allowing to both asses the e ciency of the IoT system and to discover some relationships in the observed magnitudes. A meaningful correlation between spindle speed and high-frequency vibrations was found, with Spearman coe cients over 0.7, proving the ability of the system installed to generate enough data for functional analysis of the machine.
Proyecto de Graduación (Licenciatura en Ingeniería Mecatrónica) Instituto Tecnológico de Costa Rica, Área Académica de Ingeniería Mecatrónica, 2018.
Keywords: Internet de las cosas; Máquinas CNC; Transformada rápida de Fourier; Monitoreo de condición; Plataforma de servicios; Sensores; Protocolos de serialización; Internet of things; CNC machines; Fast Fourier transform; Condition monitoring; Service platform; Sensors; Serialization protocols; Research Subject Categories::TECHNOLOGY